Numerical and biomass growth study of Bulimulus bonariensis (Rafinesque, 1833) (Gastropoda: Bulimulidae) under laboratory conditions - Díaz, Ana Carolina (2024)
Bulimulus bonariensis is considered a species of relevance to agribusiness, having beendeclared a pest with indirect damage because of its negative effects on several cropssuch as soybeans, chickpeas, and corn in central and northern Argentina. The objectiveof this work was to analyze the growth pattern of a population born under laboratoryconditions, to explore population aspects such as survival and mortality, to estimatethe age and size at gonadal maturity and first reproduction, and to contribute to theknowledge of the reproductive biology of this gastropod. From the clutches obtained,the basic biologic parameters were calculated and the individuals hatched underlaboratory conditions counted and measured every two weeks. The clutches containedan average of 44 eggs, which took about 13.7 days to hatch at a birth rate of 41.82%. Thegrowth pattern in the five clutches was analyzed individually, and the logistic modelused was the one with the highest degree of fit to that observed growth pattern, followedby the Gompertz model, and finally the von Bertalanffy model. In addition, the modelswere applied to the 102 specimens analyzed together as a cohort, where the best fittingmodel was also proved to be the logistic growth model. A concave type III survival curvewas obtained from the horizontal life table. The cohort was reduced by 48% duringthe first 50 days after birth. Beyond one month of hatching, life expectancy graduallyincreased and remained high between 65302 days of life. After day 330, life expectancydecreased and only 13.72% exceeded one year of birth, with an average length of 16.68mm. The last specimen died after 23 months at a total length of 20.24 mm, and the lifeexpectancy was estimated at almost three years. In addition, it was inferred that gonadalmaturity, when these gastropods reach 12 mm of total shell length, is reached after 200days of life. Therefore, the individuals that are born are able to reproduce for the firsttime a year after birth, when they have the approximate size of 16.68 mm.